2013
DOI: 10.1590/0004-282x20130003
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging study cannot individually distinguish individuals with mild cognitive impairment, mild Alzheimer's disease, and normal aging

Abstract: Elderly individuals with mild cognitive impairment (MCI) are part of a continuum between normal aging with its cognitive difficulties and fully-fledged dementia. However, there is a growing body of evidence suggesting that MCI might precede the onset of Alzheimer' s disease (AD). Longitudinal studies have demonstrated that subjects with MCI present a progression rate of 10-15% per year to AD, contrasting with 1-2%, in a similar analysis, in the general population using a similar age range 1 .Declarative memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(37 reference statements)
0
3
0
1
Order By: Relevance
“…[ 26 27 28 ] However, other recent studies revealed that HV difference was not significant between two groups. [ 29 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 27 28 ] However, other recent studies revealed that HV difference was not significant between two groups. [ 29 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…1 H-MRS of the hippocampal region in AD and MCI patients demonstrated a decrease in NAA and increased mI, while decreased NAA/Cr ratios were predictive of future conversion from MCI to AD [10,11]. By contrast, no significant differences in NAA/Cr, mI/Cr, and Cho/Cr of hippocampus were also found in MCI, mild AD, and normal aging [12]. Regional metabolite changes in normal ageing individuals and those with MCI and AD were reported to reflect a gradual process of brain degeneration that initially affects the left, but not right, hippocampus, resulting in asymmetry changes on 1 H-MRS [13].…”
Section: Introductionmentioning
confidence: 88%
“…[133][134][135] Studies of healthy aging, MCI, and AD are relevant in this context because they are at the interface between psychiatry and neurology; neuroimaging investigations in this field have been carried out by groups at HCFMUSP, [136][137][138] FMRP-USP, 139 and UNIFESP 140,141 in the state of Sã o Paulo, as well at the UFMG, 142 UFRJ, 143,144 and the Federal University of Pernambuco (UFPE). 145 A map of Brazil showing the official names and location of each of the institutions cited above is provided in Figure 1.…”
Section: Psychiatric Neuroimaging In Brazilmentioning
confidence: 99%